Potential bio-activity of whey fermented extract as sanitizer of organic grown lettuce. (April 2015) - Santos, M.I.S.; Martins, S.R.; Pedroso, L.; Sousa, I.; Ferreira, M.A.S.S.
Abstract: Consumption of vegetables is increasing due to demand for healthy products in peoples' diets. To reduce microbial contamination and maintain freshness, industrial processes in Portugal rely on minimally processing of vegetables with hypochlorite as sanitizer. Formation of toxic chlorine derivatives has raised concern restrictions to its use and alternatives with whey permeate as a disinfection agent has been attempted. The aim of this work was to evaluate the bio potential of fermented cheese whey, for use on disinfection of minimally processed lettuce organically grown. Assays were made with whey obtained from inoculated milk during cheese processing, fermented for 120 h at 37 °C, after which, among other carbohydrates, lactic acid was measured by HPLC, giving average yields of 18 g L −1 . The sanitizing effect of whey, undiluted, 75 and 50% solutions, was compared with 110 ppm sodium hypochlorite, after rinsing. Aerobic Microorganisms (AM), Psychrotrophic Microorganisms (PM) and Enterobacteriaceae (ENT), were used as indicators for hygiene quality. For a level of significance of P  < 0.05, the hygiene quality standards of lettuce samples, were better using 75% whey solution (AM 6.62, PM 7.48 cfu g −1 ), than using sodium hypochlorite (AM 7.48, PM 8.15 cfu g −1 ), for the 7 days of shelf life studied. Evaluation of Enterobacteriaceae showed significant differences after 3 days, between water (ENT 4.98 cfu g −1 ) sodium hypochlorite (ENT 4.81 cfu g −1 ) and 75% solution of whey (ENT 4.63 cfu g −1 ). Considering the actual limitations imposed to chlorine sanitation, these results point a good alternative to the food industry, especially for organic fresh vegetables, which are chemical free brands.